TAX POLICY OF THE FEDERAL REPUBLIC OF GERMANY - Alexander Е. Shuvalov; Anna M. Stepina (Статистика и экономика)
Considerable interest, in connection with the reform of the tax system in Russia andGermany is the tax system based on theprinciple of multiplicity of taxes and havinga federal structure. The paper presents themain types of taxes in Germany. Explores the features of Germany’s tax system and the possibility of using of certain types oftaxes in Russia.